The Effect of The Implementation of Science Park on Students' Motivation and Learning Enthusiasm - Firdatus Solehah; Suprianto Suprianto; Lutfiyatul Minnah (Lombok Institute, 2025)
This study addresses the urgent need to counter declining motivation and learning enthusiasm in physics. The research aimed to examine the effect of implementing a simple science park—organised as low-cost experimental stations—on students' motivation and enthusiasm for learning physics. Using a qualitative descriptive design with a pre–post comparison between an experimental and a control class, data were collected through classroom observations, a short test, and a motivation questionnaire. Results show that the average motivation score increased from 60% before the intervention to 80% after the science-park-based activities, supported by questionnaire responses indicating higher interest, focus, persistence in completing tasks, and reduced boredom. These findings suggest that structured, hands-on science park experiments can meaningfully enhance students' affective engagement in physics learning. It is recommended that schools and teachers adopt or adapt science park models using simple, local materials, and that future research with larger samples and more rigorous designs further investigate long-term effects on motivation, achievement, and critical thinking.